Development of the Thai Version of the iWorkHealth Assessment Tool for Work-Related Mental Health - Weeracharoen, Rachaneekorn; Untimanon, Orrapan (Disease Control Journal, 2025)
Mental health problems and work are related. Mental health problems can negatively impact work performance, and the work itself can impact a worker's mental health. This study aimed to develop a Thai version of iWorkHealth to be a screening tool for mental health problem in the workplace. The study procedures included requesting permission, translating questions, assessing the validity, trying out, and finalizing the complete instrument. The overall Cronbach Alpha coefficient was 0.65. The results of the separate assessments found that the Cronbach Alpha coefficient of general mental health, psychosocial conditions related to work, work stress and burnout, management of the organization related to mental safety and health of workers were 0.95, 0.97, 0.96 and 0.97 respectively. Although the overall Cronbach Alpha coefficient was lower than 0.70, but the Cronbach alpha coefficients of each dimension were higher than 0.90. However, the corrected item-total correlations varied from 0.21 to 1.00. Therefore, it can be used as a screening tool for mental health conditions in workplaces before referred to experts.